2020
DOI: 10.1093/forestry/cpaa013
|View full text |Cite
|
Sign up to set email alerts
|

Are there viable chemical and non-chemical alternatives to the use of conventional insecticides for the protection of young trees from damage by the large pine weevil Hylobius abietis L. in UK forestry?

Abstract: In UK forestry, the synthetic pyrethroid insecticides alpha-cypermethrin and cypermethrin have been used for many years to provide protection for young trees planted on restock sites from damage by the large pine weevil, Hylobius abietis L. However, concerns over the toxicity of these insecticides to aquatic life if misused have led to a search for alternative forms of protection. This paper describes a detailed programme of efficacy experiments undertaken between 2009 and 2015 to find replacements for these p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
38
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(44 citation statements)
references
References 25 publications
4
38
2
Order By: Relevance
“…Damage by pine weevils to planted conifer seedlings is a main threat to successful forest regeneration in large parts of Europe ( Långström and Day, 2004 ; Nilsson et al, 2010 ). Measures to counter this damage, including direct protection of plants with insecticides or protective coatings and various risk-reducing actions, are usually essential ( Nordlander et al, 2011 ; Willoughby et al, 2017 ). Complementary strategies to boost plant resistance and survival rates are currently being investigated, including the induction of plant defenses with the plant hormone methyl jasmonate ( Zas et al, 2014 ; Fedderwitz et al, 2016 ) and enhancing genetically based resistance by selecting parents with low susceptibility from breeding populations ( Zas et al, 2017 ).…”
Section: Methodsmentioning
confidence: 99%
“…Damage by pine weevils to planted conifer seedlings is a main threat to successful forest regeneration in large parts of Europe ( Långström and Day, 2004 ; Nilsson et al, 2010 ). Measures to counter this damage, including direct protection of plants with insecticides or protective coatings and various risk-reducing actions, are usually essential ( Nordlander et al, 2011 ; Willoughby et al, 2017 ). Complementary strategies to boost plant resistance and survival rates are currently being investigated, including the induction of plant defenses with the plant hormone methyl jasmonate ( Zas et al, 2014 ; Fedderwitz et al, 2016 ) and enhancing genetically based resistance by selecting parents with low susceptibility from breeding populations ( Zas et al, 2017 ).…”
Section: Methodsmentioning
confidence: 99%
“…Nevertheless, given its broad spectrum of control, the fact that it is readily taken up and translocated by plants, and that it is around 500 times less toxic to aquatic life (Willoughby et al 2017), it was thought to be a good candidate for investigation as a potential replacement for pre-planting and top-up spraying of alpha-cypermethrin and cypermethrin. The experiments reported in Willoughby et al (2020) and Moore et al (in prep. ) indicated that acetamiprid showed considerable promise for protecting trees, at least over the first year after tree planting.…”
Section: Introductionmentioning
confidence: 82%
“…In the UK, a large collaborative research programme took place between 2009 and 2017 involving public forestry administrations across Great Britain, private forestry companies, forest nurseries, and Forest Research scientists. Willoughby et al (2020) and Moore et al (in prep. ) have described some of the results from this programme, and this paper reports on further experiments in the series which examined various potential chemical and non-chemical replacements for alpha-cypermethrin and cypermethrin use in plantation forestry.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations